Prospective Kindergarten and Primary school teachers’ attitudes and beliefs on Differentiated Teaching during their Teaching Practice (Journal of Advanced Research in Social Sciences, 2019)
The aim of this proposal is the investigation of the beliefs of fourth-year students in the Department of Primary Education and the Department of Pre-School Education at the University of Ioannina – who constitute our research sample – on the issue of the implemented functionality of Differentiated Teaching within the context of Teaching Practice. The structured questionnaire was used as our research tool. The research conclusions showed that future teachers receive adequate training in the theoretical and implemented functionality of differentiated teaching but nevertheless they also revealed the limited use made of differentiated teaching during Teaching Practice and ultimately the adoption of traditional forms of instruction. While the research findings are limited, they constitute a trigger for further investigation of the issue in the teaching departments of our country. This would be especially important since the Curriculum in the Teaching Departments of the Universities, and Teaching Practice too could be reshaped in such a way that future teachers are well prepared to implement the things they were taught during their undergraduate studies.